Sociología, Derecho y desigualdades sociales. Una propuesta de docencia universitaria crítica - Almeda Samaranch, Elisabet (2019)
Critic education in human rights and social inequalities must be able to capture holistic and mutidmiensional sphere that Human Rights requires. This study introduces the basis in which critic university teaching proposal is carectarized by different active learning mechanismes with the students for the achivement of four transversal competences, specially relevant ones in this field: professional interdisciplinary, team work, problem solving and the utilization of ICTs